Legitymizacja systemu instytucjonalnego Unii Europejskiej jako organizacji międzynarodowej sui generis - Tomasz Kubin (Ksiegarnia Akademicka Publishing, 2021)
Legitimization of the institutional system of the European Union as an international organization sui generis